Global religious and secular dynamics : the modern system of classification - Casanova, José (Leiden ; Boston : Brill, 2019)
"Global Religious and Secular Dynamics offers a global historical perspective that integrates European theories of modern secularization and competing theories of global religious revival as interrelated dynamics. In the first section Casanova examines the emergence of the modern religious/secular binary system of classification within a critical review of Émile Durkheim's and Max Weber's divergent theories of religion. The modern system of classification is contrasted with the pre-axial one, in which all reality was organized according to the binary sacred/profane, and with the post-axial one, which was organized according to the binary transcendent/immanent. The second and third sections contrast the internal European road of secularization without religious pluralization with the external colonial road of global intercultural and religious encounters, particularly in Asia, that led to the global system of religious pluralism. The final section examines the contemporary intertwinement of religious and secular dynamics through the globalization of the immanent frame and the expansion of global denominationalism".
Global Religious and Secular Dynamics: The Modern System of Classification; Abstract; Keywords; Introduction; 1 Emergence of the Modern Religious/Secular Binary System of Classification; 1.1 Durkheim's Theory of Religion as the Socially Sacred; 1.2 Max Weber's Differentiation of 'Community Cults' and "Religious Communities"; 1.3 The Axial Age and "Historic" Religions; 1.4 Religion and Secular as Christian Theological Categories; 1.5 Nordic-Protestant and Southern-Catholic Patterns of Secularization; 1.6 Philosophic-Historical Secularism and European Secularization 2 The Internal Road of European Confessionalization and De-Confessionalization: Secularization without Religious Pluralism2.1 East Germany; 2.2 Catholic Poland; 2.3 Multidenominational Orthodox Ukraine; 2.4 The Russian Federation: Orthodox Confessionalism in a Multinational Context; 3 The External Road of Colonial Encounters: Formation of a World System of Religious Pluralism; 3.1 Japan; 3.2 China; 3.3 Religious Pluralization in the New World: the United States; 3.4 Quebec and Brazil as Post-confessional and Post-Catholic Societies 4 The Intertwinement of Religious and Secular Dynamics in Our Global Age: Global Denominationalism and the Globalization of the Secular Immanent Frame4.1 China; 4.2 India; 5 Conclusion; References.
Print version record.
Includes bibliographical references.
eBooks on EBSCOhost
Keywords: Durkheim, Émile -- 1858-1917; Weber, Max -- 1864-1920; Globalization -- Religious aspects; Secularism; Religions; Mondialisation -- Aspect religieux; Religions; religions (belief systems, cultures); 11.05 sociology of religion; Globalization -- Religious aspects; Religions; Secularism